Metabolomics analysis identifies different metabotypes of asthma severity. Issue 3 (30th March 2017) - Reinke, Stacey N.; Gallart-Ayala, Héctor; Gómez, Cristina; Checa, Antonio; Fauland, Alexander; Naz, Shama; Kamleh, Muhammad Anas; Djukanović, Ratko; Hinks, Timothy S.C.; Wheelock, Craig E.
In this study, we sought to determine whether asthma has a metabolic profile and whether this profile is related to disease severity. We characterised the serum from 22 healthy individuals and 54 asthmatics (12 mild, 20 moderate, 22 severe) using liquid chromatography–high-resolution mass spectrometry-based metabolomics. Selected metabolites were confirmed by targeted mass spectrometry assays of eicosanoids, sphingolipids and free fatty acids. We conclusively identified 66 metabolites; 15 were significantly altered with asthma (p≤0.05). Levels of dehydroepiandrosterone sulfate, cortisone, cortisol, prolylhydroxyproline, pipecolate and N-palmitoyltaurine correlated significantly (p<0.05) with inhaled corticosteroid dose, and were further shifted in individuals treated with oral corticosteroids. Oleoylethanolamide increased with asthma severity independently of steroid treatment (p<0.001). Multivariate analysis revealed two patterns: 1) a mean difference between controls and patients with mild asthma (p=0.025), and 2) a mean difference between patients with severe asthma and all other groups (p=1.7×10 −4 ). Metabolic shifts in mild asthma, relative to controls, were associated with exogenous metabolites ( e.g. dietary lipids), while those in moderate and severe asthma ( e.g.  oleoylethanolamide, sphingosine-1-phosphate, N-palmitoyltaurine) were postulated to be involved in activating the transient receptor potential vanilloid type 1 (TRPV1) receptor, driving TRPV1-dependent pathogenesis in asthma. Our findings suggest that asthma is characterised by a modest systemic metabolic shift in a disease severity-dependent manner, and that steroid treatment significantly affects metabolism. Mild asthma is metabolically distinct from both moderate and severe asthma, and steroid treatment affects metabolism http://ow.ly/EHo7306DwmN